Dancing with God : the Trinity from a womanist perspective - Baker-Fletcher, Karen (Chalice Press, 2006)
Karen Baker-Fletcher presents an understanding of the work of the Trinity with regard to the problem of crucifixion, a metaphor she uses for unnecessary violence. She develops a process-relational, womanist theology that considers the empathetic omnipresence of God in the midst of unnecessary suffering and the healing power of God in the movement of the Holy Spirit.